(3GdefGaSI, GdJfGaSjI hGdejRI GdJfGaSjI (B/s - (3YQbGHj, YGOds ((3GdLRGFQ(B: s (3OGQ EjdjGA ddfTQ hGdJhRjY(B, s, 2024)
(3GdefGaSI hGdJfGaSjI, GdejRI GdJfGaSjI, eMOOGJ GdejRI GdJfGaSjI MSH (B''porter''(3, fehPL bhi GdJfGaS GdNeSI d``` (B''porter''(3, GdGSJQGJjLjGJ GdYGeI ddJfGaS d``` (B''porter''(3, GdNjGQGJ GdGSJQGJjLjI GdJfGaSjIs
(3HHdjhZQGajG(B: (3U(B.(3U (B109-117s
Keywords: (3GdJfGaSjIs; (3GdefGaSIs